Attorney’s character virtues in the interaction with the principal in the course of divorcement - Barfeh , Tayyebeh; Afshani, SeyedAlireza; Fallah , Mohammad Hosein; Ruhani , Ali (Social Determinants of Health, 2021)
Introduction: The growth in such a phenomenon as divorcement has doubled the necessity of doing research thereon from various perspectives. Although numerous factors are involved in a divorcement process and they have been dealt with in the related studies, it appears that the role of the attorney as an influential factor has been considered to a lesser degree. In this study, the process of the divorcement’s formation and facilitation based on the attorneys’ character virtues has been investigated. Method: In order to develop theoretical sensitivity, the prior studies were reviewed and the extant and relevant theories were extracted and discussed. Using qualitative method and grounded theory and through subjective and purposive sampling, 18 divorced Yazdi women who had hired lawyers were selected and subjected to deep interviews. Results: The 5 categories of wisdom, honesty, fairness, Humbleness and Transcendence move the clients’ cases towards compromise. The 5 categories of enlightenment, meticulousness, futurisms, social intelligence and effective communication had a dual role. The case, at the discretion of the lawyer and the client, could lead to both compromise and divorce. 5 categories of love for learning, creativity, chivalrousness, stability and leadership also lead to divorce. Conclusion: Attorneys with character virtues help the client make the most beneficial decision through positive interaction and confidence transfer